Influence of nanosized incoherent particles on dislocation annihilation in heterophase aluminum-matrix crystalline alloys - Daneyko, Olga I.; Kovalevskaya, Tatiana A.; Shalygina, Т. А.; Simonenko, V. G. (Russian physics journal)
Using mathematical modeling, patterns of changing the densities of dislocation subsystem components in dispersion hardened materials have been revealed depending on the volume fraction and scale characteristics of the hardening phase at different deformation temperatures. It has been shown that in all examined materials with hardening particles of different sizes, the dislocation annihilation significantly decreases with the volume fraction of nanosized incoherent particles. It has been found that the dislocation density in prismatic loops is largely determined by the particle sizes and the volume fraction of the hardening phase.